Football – Novel Approaches to Tackle Diabetes - Müssig, Karsten; Adamek, Henning E. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Balanced diet and regular physical activity are of key importance to the prevention of the development and progression of non-communicable diseases. In 2050, 50% of the European population is expected to be obese. Cardiovascular diseases, diabetes mellitus, cancer, as well as joint impairments, will further increase. Therefore, programmes are critical to the improvement of the population’s health status in the long run. New ways have to be found that allow addressing more people than with the current approaches. Football has a great potential to attract people at risk for or with already existing non-communicable diseases, such as type 2 diabetes, to participate in health-promoting programmes. The novel football version, walking football was developed for elderly players, aiming at avoiding injuries and physical overload. The present article gives a brief overview on the metabolic effects of recreational football, particularly walking football, as well as health-promoting programmes offered by professional football clubs in humans at risk for or with already existing non-communicable diseases.
Keywords: physical exercise; walking football; non-communicable diseases; obesity; health promotion programmes